An Improved Feasibility Analysis of Photovoltaic Array Configurations and Reconfiguration Under Partial Shading Conditions. Issue 9 (3rd October 2020) - Jalil, Mohd Faisal; Khatoon, Shahida; Nasiruddin, Ibraheem; Bansal, Ramesh Chand
Abstract : Abstract— Globally, the shading phenomenon has been identified as one of the major issues relating to the successful and effective operation of photovoltaic (PV) system. Shading can be due to neighboring development, passing mists, fowls or winged animals' litter, etc. that will decrease the generation of PV system. The PV generations under partial shading can be enhanced by suitably selecting PV array configuration and reconfiguration schemes. This article provides an extensive investigation of various PV array configurations and reconfiguration operating in partial shading conditions. The competence with reference to maximum power output, shading losses, fill factor, and mismatch losses of PV array configuration, i.e., Series-Parallel (SP), Honey-Comb (HC), Total Cross Tied (TCT), Bridge-linked (BL), and reconfiguration namely; Odd–Even (OE) are evaluated for four different shading case studies. The results are compared with 7 × 7 PV array configuration for the same shading cases. The investigation is expanded to identify the outcomes of incorporating a bypass diode in each module on power output. The investigations carried out also reveal that the shading scenario decides the maximum instantaneous power output of PV array. The outcomes exhibit that OE reconfiguration provides improved performance concerning to maximum power generation for all considered shading case studies.